2010
DOI: 10.1007/s00726-010-0759-0
|View full text |Cite
|
Sign up to set email alerts
|

Zinc induces disorder-to-order transitions in free and membrane-associated Thellungiella salsuginea dehydrins TsDHN-1 and TsDHN-2: a solution CD and solid-state ATR-FTIR study

Abstract: Dehydrins are intrinsically unstructured proteins that are expressed in plants experiencing extreme environmental conditions such as drought or low temperature. Although their role is not completely understood, it has been suggested that they stabilize proteins and membrane structures during environmental stress and also sequester metals such as zinc. Here, we investigate two dehydrins (denoted as TsDHN-1 and TsDHN-2) from Thellungiella salsuginea. This plant is a crucifer that thrives in the Canadian sub-Arct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 93 publications
2
38
0
Order By: Relevance
“…Actinidia chinensis DHN1 is normally located in the nucleus and then moves to the cytoplasm near the plasma membrane in response to osmotic stress (Qiu et al, 2001). Based on available evidence, DHNs move toward the plasma membrane and intracellular membrane systems during cold acclimation, a result that is consistent with DHNs’ binding gain of membrane stability in vitro (Koag et al, 2003, 2009; Rahman et al, 2010, 2011a,b; Rahman, 2012). However, our results conflict with this notion.…”
Section: Discussionsupporting
confidence: 53%
“…Actinidia chinensis DHN1 is normally located in the nucleus and then moves to the cytoplasm near the plasma membrane in response to osmotic stress (Qiu et al, 2001). Based on available evidence, DHNs move toward the plasma membrane and intracellular membrane systems during cold acclimation, a result that is consistent with DHNs’ binding gain of membrane stability in vitro (Koag et al, 2003, 2009; Rahman et al, 2010, 2011a,b; Rahman, 2012). However, our results conflict with this notion.…”
Section: Discussionsupporting
confidence: 53%
“…Using synthetic peptides, Hara et al (2005) showed that there is no ion binding to the K-segments, and that the strongest binding is to the sequence HKGEHHSGDHH, likely due to the His-His dipeptides. A similar study was carried out by Rahman et al (2011) with TsDHN1 and TsDHN2 using isothermal calorimetry (ITC) to characterize metal binding. In the presence of Zn(II), it was shown that there were two zinc binding sites on TsDHN1 with a K d of 45 μM, while there was one zinc binding site on TsDHN2 with a K d of 26 μM.…”
Section: Dehydrin Ligandsmentioning
confidence: 85%
“…The functions of LEA proteins have been characterized mainly by in vitro experiments. These include binding of metal ions (Heyen et al, 2002;Hara et al, 2005;Rahman et al, 2011b) or lipid vesicles (Koag et al, 2003;Kovacs et al, 2008;Rahman et al, 2010), hydration or ion sequestration (McCubbin et al, 1985;Tompa et al, 2006), and, remarkably, stabilization of proteins and membranes in adaptation to abiotic stress ( Figure 2A, I to III). The latter function includes protection of various proteins against heat-induced inactivation or aggregation under stress conditions (Haaning et al, 2008;Boucher et al, 2010) and protection of membranes against drying and chilling (Tolleter et al, 2007;Rahman et al, 2010;Tolleter et al, 2010).…”
Section: Lea Protein Function In Response To Abiotic Stressmentioning
confidence: 99%
“…Different dehydrins have also been found to have multiple modes of ion binding: The acidic group 2b LEA dehydrins show phosphorylation-dependent metal-ion binding (Alsheikh et al, 2005), whereas Cu-COR15 (for Cold-Regulated) from Citrus unshiu shows metal-ion binding without phosphorylation (Hara et al, 2005). Some LEA proteins acquire secondary structure through bindinginduced folding upon binding to partners, metal ions, and model membranes (Koag et al, 2009;Rahman et al, 2010Rahman et al, , 2011b or upon drying (Boudet et al, 2006;Thalhammer et al, 2010;Popova et al, 2011), whereas for other dehydrins, neither temperature, metal ions, nor stabilizing agent promoted structural folding (Mouillon et al, 2006). It seems the role of the conserved segments within these nonfoldable dehydrins is to act as beads on a string for specific recognition or interaction with membranes rather than promoting tertiary structure formation.…”
Section: Lea Protein Function In Response To Abiotic Stressmentioning
confidence: 99%